Exploration for stratabound copper, lead and zinc deposits in the Damara-Katanga orogen, central-southern Africa - Latorre, J J (Rhodes University, Faculty of Science, Department of Geology, 1992)
The Damara-Katanga orogen in central-southern Africa represents an area of 1.73xl0â ¶ sq. km. The region is considered one of the wealthiest metallogenic provinces in the world. Successful exploration for stratabound base-metal deposits has taken place at this particular area since the introduction of more organised methodology in the early 1920s. The genesis, location and distribution of the ore deposits are related to their tectonic settings. Geodynamic evolution of the orogen, which initially formed part of a complex Pan-African rift system, comprises the following stages rifting; downwarping, including spreading on the western portion; syn-orogeny and late-orogeny. Two major tectonic events in the history of the region have been identified: the Katangan (900-750 Ma) and the Damaran episodes (750-500 Ma). Timing of mineralisation of ore deposits has been related to the evolutionary stages of the orogen. Genetic models of the most productive deposits are briefly discussed in this dissertation. The sedimentological, geochemical, paleogeographic and structural features can be employed as geological guidelines for integrated exploration programmes. Discoveries of major deposits and prospects in the orogen are also summarised, focussing on the exploration methods employed. The cost-effective use of the exploration techniques includes the classical copper-lead-zinc soil sampling for residual soils such as those in the Copperbelt area. Airborne magnetics and electromagnetics and follow-up ground geophysics have proved successful in areas where the cover is transported in the search for shallow ore deposits such as the Matchless massive sulphides. Remote sensing, geochemical and geophysical techniques have been tried in covered areas of western Botswana. The lack of geological control makes this interpretation difficult. A detailed geological mapping and the use of geochemical and geophysical techniques has been used to delineate carbonate-hosted base-metal deposits at the Otavi Land. The more expensive traditional methods necessary for the delineation of orebodies, such as pitting, trenching and drilling, are also discussed. Using a sequential approach, a possible exploration strategy is suggested, outlining the cost-effective use of remote sensing, geochemical and geophysical techniques. Standardisation in basic geological information is required for future successful explorations in the Damara-Katanga orogen, as well as attractive mining policies. In the event of their implementation, exploration perspectives are promising, specifically in terms of ore potential.
Keywords: Mining geology -- Research -- Africa; Copper ores -- Africa; Lead ores -- Africa; Zinc ores -- Africa